(untitled) (Tempo e Argumento, 2021)
This article starts from the perception of inequality as a central theme in History Teaching, in connection with situations of conflict and violence. Inequality is analyzed here as being situated in many contexts, it is produced from some social markers of difference that we have selected, i.e. class, race, gender, generation, religious belonging, region and place of residence, and their intersection modalities. The strategy of education on sensitive topics in History Teaching is then presented as a pedagogical alternative to address inequality as a theme. The discussion is based on collection of accounts and observation of scenes from online classes during the pandemic period, which caused strong tension in the ways of living the school culture and the school daily routine, accentuating inequalities, but also indicating escape routes. In possession of elements collected in this way, a redefinition of the concept of education on sensitive topics is proposed, then shifting to the perception of sensitive relationship-making. This article deals with the present time, history taught, situations of inequality, and education on sensitive themes, being set in the pandemic period. Keywords: History Teaching; Sensitive topics; Inequality; Violence; School curriculum.